Pengaruh Harga, Kualitas Produk, Dan Promosi Terhadap Keputusan Pembelian Produk Smartphone Oppo (Studi Pada Mahasiswa UMS) - Radete, Bagus Pebrianto, Dra. Wuryaningsih Dwi Lestari, M.M (2015)
This purpose of this research is to analyze the impact of price, product quality, and promotion their effects toward buying decision on Oppo smartphone, where price (X1), product quality (X2), and promotion (X3) become independents variables and buying decision (Y) as a dependent variable. The population of this research is UMS college. Sample that used in this research are 100 respondents while its primary method used questionaires. Then analyzed method that used in this research includes validity test, reliability test, classical assumption test, multiple linear regression, t-test, F-test, and coeffcients of determination test. Statistic data analysis, indicators in this research showed that all data were valid and reliable. Hypothesis testing used t-test showed that the price, product quality, and promotion significantly influences its buying decision.